مالی کرپشن کا خاتمہ اوراسلامی معاشی اصول وضوابط؛ایک تجزیاتی مطالعہ: Islamic economic principles and the elimination of financial corruption; An analytical Study - Ali, Dr. Asjad; Aleem, Dr. Abdul (Al-Amīr Research Journal for Islamic Studies, 2024)
The religion of Islam is a complete and perfect code of life. Its teachings provide perfect guidance for all walks of life. They are telling the people that whenever Islamic principles and teachings were adopted, their definite effects became an indisputable fact and made a glorious history. The economic principles of Islam not only have the potential to eradicate financial corruption but also They also eliminate social evils. Therefore, in this article, first of all Islamic economic principles will be explained, such as the provision of sustenance by Allah, the distinction between halal and haraam, the limits of earning and spending wealth, the prohibition of usury, the incentive of debt, halal trade and haraam trade. All these principles and teachings will be explained in such a way that the benefits and fruits will be appreciated and people will not feel the need to go in the wrong direction. Then at the same time different cases of financial corruption such as theft, robbery, gambling, bribery, embezzlement, fraud and usury etc. will be explained in such a way that our lives will be free from all these cases of corruption. I run out of blessings, so problems and worries keep growing and restlessness makes life miserable. Keywords: economic principles, corruption, institutions, trade, halal and haraam, social evils, distribution of wealth, effects, good blessings, interest.